The effect of online-based assignment responses and student creativity in PJOK during pandemic in rural and urban area - Padli Padli; Yanuar Kiram; Irfan Arifianto; Yogi Setiawan; Jeki Haryanto; Heru Syarli Lesmana (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
Creativity is an ability that must not be lost during a pandemic. The purpose of this study is to find out whether there is an influence of online-based task responses to students' creativity during the pandemic period and the difference is based on students living in rural and urban area. This type of research is a mixed method collected through an online-based assignment response questionnaire instrument, student creativity questionnaire instrument, and interview instruments. The sample of this study was a student of the 2017 physical education, health and recreational education program at Padang State University with a number of 68 students. The data analysis technique in this study uses descriptive statistical testing and simple linear regression testing. The results of this study indicate that there is an influence between online-based task response to 51.5% creativity. Furthermore, online task-based response category is either dominated by students living in urban areas with a percentage of 72.2%. Then review based on student creativity during a pandemic period for students living in urban areas categorized both with a percentage of 84.2% while students who live in ranked are considered less good with a percentage of 54.5%. This research is expected to contribute to the world of education today and can change the perspective of the community or an individual regarding the positive impact of the online assignment given to students in the pandemic period.